Analysis of the Influence of Process Performance on Organizational Performance: Evidence from Romania - Andreea BARBU; Gheorghe MILITARU; Valentin-Andrei MĂNESCU; Ramona Alexandra NEGHINĂ; Mihaela-Rodica GANCIU (Communications of International Proceedings, 2020)
Performance is a key concept for any organization, and lately, it has begun to become a priority for both business management and researchers. Managers want to provide the best products and services to customers, increasing the company's revenues, but at the same time, they aim to streamline their internal operations, reduce costs and increase the company's productivity. The researchers come to the aid of the companies and carry out activities to understand what influences the performance of the company, what is the level of performance of the company and what could be the most effective methods for a company to improve its performance. The problem is that there are not many papers that analyse how exactly some processes affect business performance and what processes contribute the most to increase business performance. Thus, the main objective of this paper is to determine the most important processes within the service companies that contribute to increase organizational performance. In this regard, the authors used quantitative research to analyse 8 main processes from a service company. The results highlighted the fact that every process can improve the organizational performance by improving its process performance, but there are a few processes that are more important for companies than others. Thus, the management of the service companies should pay more attention to processes like human resources management, marketing and sales, and the financial-accounting process, those being processes that influence the most the organizational performance.
Keywords: Service company performance; business process performance; performance; processes performance.